Molecular Detection of Mycoplasma Gallisepticum and Mycoplasma Synoviae Infection in Poultry - Waqar Mazhar (Journal of Food Science and Hygiene, 2022)
In Pakistan, production of poultry has been evolved as a good alternate of beef and mutton. In this study multiplex PCR approaches were adopted to differentiate and detect avian mycoplasma in a single PCR reaction as a step forward in the economization of PCR detection. From the total of 25 samples, 25 (100%) had a positive Mycoplasma isolation result. The biochemical test yielded the highest number of isolations, with MG accounting for 10/25. Commercial DNA-based PCR kits have been developed as a result of recent advancements in diagnostic techniques for Mycoplasma infections. Tetracyclines, fluoroquinolones, tilmicosin, tylosin, spiramycin Infections should be reduced as much as possible.
Keywords: Poultry